Isozyme analysis of Philippine bananas implications on their evolutionary pathway and classification - Espino, Rene Rafael C. (2000)
Isozyme analysis was conducted on banana using malate dehydrogenase (MDH), phosphoglucomutase (PGM), phosphogluconate dehydrogenase (PGD), glutamate dehydrogenase (GDH), glutamate oxaloacetate transaminase (GOT) and shikimic acid dehydrogenase (SkDH). Results showed that cultivars belonging to the BB/BBB genome were distinct from those cultivars in the AA/AAA genome based on their banding patterns in MDH, GOT, GDH and to some extent in SkDH. Moreover, genetic variation was also observed in the two wild-seeded M. balbisiana cultivars ('Butuhan' and 'Balayan'). It is postulated that edibility arose in M. balbisiana independent from that in M. acuminata; a modified evolutionary pathway for cultivated bananas is proposed.
Keywords: Philippine bananas